2015
DOI: 10.21660/2015.16.4369
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Freezing Effect on Unconfined Compression Strength and Permeability of Saturated Granular Soils

Abstract: Artificial ground freezing usage gradually rises in civil engineering applications as a soil supporting system. However, many unknown fundamental parameters have been still waiting discovery, especially for granular soil. Granular soil can not carry its own weight during unconfined conditions. If water turns to ice that locates in the soil pores, it proceeds as a cementitious material. First step of design phenomena is to identify the material properties in geotechnical engineering. Within this scope, unconfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Many researchers have studied AGF and its effects on soil properties and mechanical behavior of frozen soils [20][21][22][23][24][25][26][27][28][29]. However, compared with unfrozen soils a greater effort is required to study frozen soils [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied AGF and its effects on soil properties and mechanical behavior of frozen soils [20][21][22][23][24][25][26][27][28][29]. However, compared with unfrozen soils a greater effort is required to study frozen soils [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The values of coefficients of permeability obtained may be influenced by (1) textural properties (i.e., pore size/ grain size, grain size distribution, the shape of grains and packing of grains), ( 2) gas slippage, (3) amount distribution and type of clays, (4) type and amount of secondary porosity, (5) overburden pressure, (6) reactive fluids, and (7) highvelocity flow effects. The coefficient of permeability determined in this work was compared with the standard coefficient of permeability values of soil Evirgen et al (2015). This showed that the host of the PHCs is composed of silty clay.…”
Section: Results and Discussion Of The Porosity And Coefficient Of Permeability Testmentioning
confidence: 92%
“…For sample 1, the average of the two values obtained was 8.03×10 -7 , and for sample 2, the average of the two values obtained was 8.19×10 -7 . These values obtained are indicative of clay, according to standard chart of permeability coefficient for various soil types [19].…”
Section: Permeability Testmentioning
confidence: 97%